Milk yield of Sudanese cattle as affected by the age of the cow - Khalifa, H.A.; El-Shafei, M.M. (1965)
The influence of age of animal and age at first calving on milk production in the Butana and Kenana cattle of the Sudan was investigated at Atbara dairy farm and Um Binein centre. The Butana cattle reached their maximum production in the sixth lactation, according to the lumped and paired methods 47% and 45% respectively more than the first lactation yield. Age at first calving showed a highly significant influence on the average production for the first six lactations. The Butana cattle had first calving at 50.3 ± 2.8 months, while the Kenana cattle at 42.9 ± 0.8 months. Butana showed a negative significant correlation (-0.440) between age at first calving and first lactation production, while in the Kenana the correlation coefficient was positive but not significant (0.356). Age at first calving has no significant influence on first lactation milk yield.